The mixed cropping of Anthocephalus cadamba and Glycine max for rehabilitating sloping lands - KARYATI KARYATI; SRI SARMINAH; KARMINI KARMINI; GUNAWAN SIMANGUNSONG; JEKSON TAMBA (Society for Indonesian Biodiversity, 2018)
Karyati, Sarminah S, Karmini, Simangunsong G, Tamba J. 2018. The mixed cropping of Anthocephalus cadamba and Glycine max for rehabilitating sloping lands. Biodiversitas 19: 2088-2095. Agroforestry system is one of the many alternatives to overcome problems concerning sloping lands. The objectives of this current study were to analyze the effect of agroforestry system in the form of mixed cropping of jabon tree (Anthocephalus cadamba Mig) and soybean (Glycine max Merr) on growth and hydro-orological aspects on sloping lands with different steepness (a slightly steep and a steep slope gradient). The growth parameters (survival rate, ground coverage, diameter increment, and height increment) and hydro-orological parameters (surface runoff, potential erosion, erosion hazard index, and erosion hazard level) were observed in this study. The findings showed that on the slightly steep slope (>15-25%) land, the survival rate of A. cadamba was 90%, the ground coverage of the G. max was 70-79%, the diameter and the height increments of A. cadamba trees were 1.8 cm year-1 and 13.8 cm year-1 respectively. Meanwhile, the potential erosion rate and the erosion hazard index were 32.13 ton ha-1 year-1 and 1.29, respectively. In the steeper slope (>25-45%), the survival rate of A. cadamba reached 90%, the G. max ground cover reached 60-69%, the diameter and height increments of the A. cadamba reached 1.5 cm year-1 and 12.0 cm year-1 respectively. Furthermore, in the steep slope, the potential erosion rate was 52.51 ton ha-1 year-1 and the erosion hazard index was 2.10. In addition, the potential erosion rate and the erosion hazard index in the control plot were higher than those in slightly steep slope. Therefore, it could be implied that the application of A. cadamba and G. max mixed cropping system could rehabilitate sloping lands.